factorise:6p^{2}+11p-10 Share with your friends Share 2 Saniya Fatima answered this 6p^{2}+11p-106p^{2}+15p-4p-103p(2p+5)-2p(2p+5)(3p-2)(2p+5) 2 View Full Answer Amal Prasad answered this 6p^{2}+11p-10 =6p^{2}+15p-4p-10 =3p(2p+5)-2p(2p+5) =(3p-2)(2p+5) 0 Vibhav Agarwal answered this 6p^{2}+11p-10 =6p^{2}+15p-4p-10 =3p(2p+5)-2p(2p+5) =(3p-2)(2p+5) 0 Manasvi Bhat answered this In the above answers, the third step is incorrect. It should be 3p (2p + 5) - 2 (2p + 5) instead of 3p (2p + 5)- 2p (2p + 5)The correct steps are:6p^{2} + 11p - 10 =6p^{2}+15p - 4p - 10 =3p (2p + 5) - 2 (2p + 5) =(2p + 5) (3p - 2) 1 Samrood Saleem K answered this In the above answers, the third step is incorrect. It should be 3p (2p + 5) - 2 (2p + 5) instead of 3p (2p + 5)- 2p (2p + 5) The correct steps are: 6p^{2} + 11p - 10 =6p^{2}+15p - 4p - 10 =3p (2p + 5) - 2 (2p + 5) =(2p + 5) (3p - 2) 0 Samrood Saleem K answered this In the above answers, the third step is incorrect. It should be 3p (2p + 5) - 2 (2p + 5) instead of 3p (2p + 5)- 2p (2p + 5) The correct steps are: 6p^{2} + 11p - 10 =6p^{2}+15p - 4p - 10 =3p (2p + 5) - 2 (2p + 5) =(2p + 5) (3p - 2) 10